Effects of biotic interactions on plant fecundity depend on spatial and functional structure of communities and time since disturbance. (26th October 2022) - Walter, Hanna E.; Pagel, Jörn; Cooksley, Huw; Neu, Alexander; Schleuning, Matthias; Schurr, Frank M.
Abstract: Biotic interactions in plant communities affect individual fitness and community dynamics. Interactions between plants vary in space, over time and with organisational complexity. Yet it is challenging to quantify temporal, spatial and functional determinants of different types of interactions between long‐lived perennial plant species and their effect on lifetime fecundity. We studied how plant–plant, pollinator‐ and seed predator‐mediated interactions affect year‐to‐year variation in three fecundity components (cone production, seed set and seed survival) during post‐fire recovery. Age‐stratified data on the three fecundity components were collected in 19 even‐aged communities comprising 20 serotinous Protea shrub species in the South African Fynbos. We analyse data on these fecundity components with neighbourhood models to infer the sign and strength of interactions throughout post‐disturbance recovery, the neighbour plant traits that shape them and the spatial scale at which interactions take place. For each fecundity component, these models describe how neighbourhood effects change over time and with spatial distance between plants. We then predicted neighbourhood effects on individual fecundity components and cumulative reproductive output at different post‐fire stand ages for each focal plant. Competitive effects on cone production and seed set increased with post‐fire stand age as biomass and floral resources for pollinators build up. In contrast, neighbourhood effects on seed survival were weak throughout post‐disturbance recovery. Plant–plant interactions were shaped by neighbour traits related to resource acquisition, whereas animal‐mediated interactions depended on neighbour traits related to resource availability for pollinators and seed predators. The spatial scale of the interactions increased from plant–plant over predator‐mediated to pollinator‐mediated interactions. The joint effect of these interactions on cumulative reproductive output caused the proportion of focal plants experiencing competition to increase with time since fire. Synthesis . We show that temporal changes in biotic interactions throughout post‐disturbance recovery of perennial plant communities depend on functional traits and can be integrated into neighbourhood effects on lifetime fecundity. Studying the temporal, spatial and functional determinants of neighbourhood effects on lifetime fecundity is important for predicting not only individual plant fitness but also population and community dynamics in changing environments. Abstract : Plant–plant and animal‐mediated interactions that affect yearly fecundity of perennial plants in even‐aged communities depend on the spatial and functional structure of the community and time since disturbance. Furthermore, temporal changes in these biotic interactions can be integrated into neighbourhood effects on lifetime fecundity.